2022
DOI: 10.1186/s12888-022-04156-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the relative sensitivity of two dimensional personality models to the psychopathological symptoms: the section III DSM-5 maladaptive traits versus affective temperaments

Abstract: Background The Personality Inventory for DSM-5 (PID-5) and Temperament Evaluation of Memphis, Pisa, Paris, and San Diego Autoquestionnaire (TEMPS-A) are tools designed for personality dispositions for mental health symptoms. The present study was conducted to compare these models in terms of their relative sensitivity to the symptoms of personality disorders (PDs) and non-personality disorders (NPDs). Methods Subjects in this cross-sectional study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
4
1
Order By: Relevance
“…The results of the present study supported this hypothesis and data analysis using factor analytical techniques showed that the symptoms of PDs and CDs are two independent factors. Although this finding is inconsistent with the current literature in psychopathology (Kotov et al, 2017;Gluschkoff et al, 2019;McCabe et al, 2022), it is consistent with the findings of some studies in Western and non-Western samples (Bachrach et al, 2012;Komasi et al, 2022). The present results suggest that, although it is possible to synthesize psychopathological differences into a single framework (Kotov et al, 2017), there is nevertheless a difference between PDs and CDs.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…The results of the present study supported this hypothesis and data analysis using factor analytical techniques showed that the symptoms of PDs and CDs are two independent factors. Although this finding is inconsistent with the current literature in psychopathology (Kotov et al, 2017;Gluschkoff et al, 2019;McCabe et al, 2022), it is consistent with the findings of some studies in Western and non-Western samples (Bachrach et al, 2012;Komasi et al, 2022). The present results suggest that, although it is possible to synthesize psychopathological differences into a single framework (Kotov et al, 2017), there is nevertheless a difference between PDs and CDs.…”
Section: Discussioncontrasting
confidence: 82%
“…In other words, our search was fruitless to find studies that compared the contribution of PDs and CDs to the manifestation of pseudo-cardiac symptoms and comorbid conditions such as poor sleep quality. Although the current dimensional frameworks in psychopathology propose the integration of all mental disorders, including PDs and CDs (Kotov et al, 2017), such a claim cannot be definitively accepted until sufficient empirical evidence is provided (Komasi et al, 2022). Therefore, we sought to answer the question of whether factor analysis supports a one-factor or two-factor structure for the symptoms of PDs and non-PDs.…”
Section: The Study Aimsmentioning
confidence: 98%
“…It can be argued that these data also feature psychoticism as a core trait domain posits as a general factor of personality disorder [45][46][47], or as a core personality dysfunction [48]. In this follow-up, there is evidence that psychoticism can capture clinically relevant aspects of severe mental illness associated with psychosis and other related characteristics, indicating possibly shared patterns of personality expression [14,49], demonstrating a degree of non-specificity in the patterns across symptoms of personality disorders and non-personality disorders, similarly to some other evidence in the literature [49].…”
Section: General and Common Main Findings Of Borderline Pd And Bipola...mentioning
confidence: 75%
“…Recent reports addressed strong cross‐sectional and longitudinal associations between disinhibition and both antisocial and borderline diagnoses (Caspi, 1996; Kyranides et al, 2017; Mullins‐Sweatt et al, 2019; Nigg et al, 2005). Furthermore, disinhibition is associated with a range of psychiatric disorders such as substance use disorders, impulse control disorders, and PDs (Hemmati et al, 2019; Jakubczyk et al, 2018; Komasi et al, 2022, 2023; Krueger et al, 2002; Perrotta, 2020). Therefore, disinhibition can serve as a useful marker for identifying individuals who may be at risk for developing clinical disorders or who are already experiencing clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%